Methanol-Sensing Property Improvement of Mesostructured Zinc Oxide Prepared by the Nanocasting Strategy. (13th February 2013) - Gao, Qian; Zheng, Wei-Tao; Wei, Cun-Di; Lin, Hui-Ming
Abstract : The specific structure and morphology often play a critical role in governing the excellent intrinsic properties of the compound semiconductor. Herein, mesostructured ZnO with excellent methanol-sensing properties was prepared by a structure replication procedure through the incipient wetness technique. The investigation on the crystal structure and morphology of the resultant material shows that the product consists of hexagonally arranged mesopores and crystalline walls, and its structure is an ideal replication of CMK-3 template. Consequently, mesostructured ZnO was fabricated as a gas sensor for methanol. The excellent methanol-sensing performance was achieved at a relatively low operating temperature of 120°C. In comparison with the nonporous ZnO prepared through conventional coprecipitation approach, mesostructured ZnO material shows the higher sensitivity and stability. Furthermore, it shows the discrimination between methanol and ethanol sensitivity, which makes it a good candidate in fabricating selective methanol sensor in practice.